Combining treatment with myo-inositol and D-chiro-inositol (40:1) is effective in restoring ovary function and metabolic balance in PCOS patients. (2nd January 2017) - Monastra, Giovanni; Unfer, Vittorio; Harrath, Abdel Halim; Bizzarri, Mariano
Abstract: Polycystic ovary syndrome (PCOS), a relevant cause of infertility, is a heterogeneous, endocrine disorder affecting up to 10–15% of women in reproductive age. Besides hyperandrogenism, insulin resistance (IR) plays a key role in such syndrome. Insulin-sensitizing drugs, such as Metformin, are effective in treating hyper-insulinemic PCOS patients. Recently, inositols – myo-inositol (MI) and D-chiro-inositol (DCI) – have shown to be an efficient and safe alternative in PCOS management, as both inositol isoforms are able to counteract downstream consequences of insulin resistance. Yet, whereas DCI contributes in mediating insulin activity mainly on non-ovarian tissues, MI displays specific effects on ovary, chiefly by modulating glucose metabolism and FSH-signaling. Moreover, MI may also improve ovarian functions by modulating steroid metabolism through non-insulin-dependent pathways. As DCI and MI activity likely involves different biological mechanisms, both inositol isoforms can be synergistically integrated according to a multitargeted design, by combining MI and DCI in a ratio corresponding to their physiological plasma relative amount (40:1). New experimental and clinical evidence with MI plus DCI evidenced the suitability of such integrated approach, and provided promising results. Further studies need to investigate thoroughly the molecular mechanism and confirm such preliminary data.